Seamless phase IIa/IIb adaptive design with the same primary endpoint for proof of concept and dose finding - Yuan, Jiacheng (Contemp Clin Trials Commun, 2018)
This paper considers combining a proof of concept (POC) study and a dose finding (DF) study where the POC and the DF share the same primary endpoint. An example based on real study conditions shows that compared to a conventional design the proposed adaptive design tests more active doses, with a smaller sample size and a shorter overall duration leading to a budget saving of 30% in study operations.